The Use of Science Reflective Journal Writing by JAS Approach to Train Students Metacognitive Ability - Septina, Esky Purba; Marianti, Aditya; Widiatningrum, Talitha (FMIPA UNNES, 2018)
This research aims to train students’ metacognitive ability used Science Reflective Journal Writing by JAS approach on the material of reproductive system. This type of research was One shot case study which was conducted at SMA Negeri 2 Pemalang. The subjects of this research were students of grade XI MIA 4 and XI MIA 5. The Independent variable of this research was Science reflective journal writing in problem-based learning by JAS approach, while dependent variables were metacognitive ability, activity and students’ cognitive learning results. The students’ metacognitive ability was measured by using observation sheets of students’ activity, discussion assessment sheets, and post-test questions. The results of analysis showed that the use of science reflective journal writing has good influence to train the students’ metacognitive ability. The students’ metacognitive ability of  SMA Negeri 2 Pemalang was included in good category which is 76% , it also gave an influence to cognitive learning result with mastery learn classical ≥ 75% and student activity with a range of 62.51% - 81.25% classified as active. Based on the results of the research, it can be concluded that the students’ metacognitive ability at SMA Negeri 2 Pemalang for reproductive system material classified as good on the aspects of describing, interpreting, evaluating, planning, and also has good influence to the activity and students’ cognitive learning results on the material of reproductive system.